Research on the Intention to Purchase of Fabric Saints : Based on the Theory of Consumption Value, Green Purchase Intention, and Green Purchase Behaviour - Gleny; Bernardo, Innocentius (Pandawan, 2023)
The purpose of this study is to determine: 1) whether functional values have a positive effect on green purchase intention, 2 ) whether social values have a positive effect on green purchase intention, 3 ) whether emotional values have a positive effect on green purchase intentions, 4) whether social values have a positive effect on positive effect on green purchase intention, 5) whether the epistemic value has a positive effect on green purchase intention, 6) whether green purchase intention has a positive effect on green purchase behavior. This research was conducted on women who know about the existence of cloth sanitary napkins. The survey method was carried out in this study. Data was collected by collecting questionnaires. The number of samples obtained in this study was 162 samples. The sampling technique was done by convenience sampling. Partial Least Square- Structural Equation Modeling approach with the SmartPls program is used in this research. The results showed that the functional, social, and epistemic values did not have a positive effect on green purchase intention. Emotional and conditional values have a positive effect on green purchase intention. Green purchase intention has a positive effect on green purchase behavior.